2005
DOI: 10.1128/aem.71.7.3617-3623.2005
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic Engineering of Anthocyanin Biosynthesis in Escherichia coli

Abstract: Anthocyanins are red, purple, or blue plant pigments that belong to the family of polyphenolic compounds collectively called flavonoids. Their demonstrated antioxidant properties and economic importance to the dye, fruit, and cut-flower industries have driven intensive research into their metabolic biosynthetic pathways. In order to produce stable, glycosylated anthocyanins from colorless flavanones such as naringenin and eriodictyol, a four-step metabolic pathway was constructed that contained plant genes fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
70
0
1

Year Published

2005
2005
2018
2018

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 136 publications
(72 citation statements)
references
References 27 publications
1
70
0
1
Order By: Relevance
“…The gene encoding dihydroflavonol reductase (At5g42800) was also up-regulated in pdx1.3 leaves compared with the wild type (4.52-fold). The latter is considered to be a rate-limiting step (Das et al, 2012) late in anthocyanin biosynthesis and is a target of PAP1 and PAP2 (Yan et al, 2005). On the other hand, no significant changes in the expression of GL3, TT8, or MYBL2 were observed compared with the wild type in the microarray.…”
Section: Suppression Of Pdx11 Expression By Sucmentioning
confidence: 80%
“…The gene encoding dihydroflavonol reductase (At5g42800) was also up-regulated in pdx1.3 leaves compared with the wild type (4.52-fold). The latter is considered to be a rate-limiting step (Das et al, 2012) late in anthocyanin biosynthesis and is a target of PAP1 and PAP2 (Yan et al, 2005). On the other hand, no significant changes in the expression of GL3, TT8, or MYBL2 were observed compared with the wild type in the microarray.…”
Section: Suppression Of Pdx11 Expression By Sucmentioning
confidence: 80%
“…In vitro experiments with recombinant LDOX suggested that the enzyme could produce not only its natural product, cyanidin, but depending on the C-4 stereochemistry of the leucocyanidin substrate, possibly also dihydroquercetin and quercetin (Turnbull et al 2003). Also, Xavonols could be observed as a side product in Escherichia coli cells simultaneously expressing recombinant F3H, DFR, LDOX and a Xavonoid 3-O-glucosyltransferase, potentially due to an alternate reaction catalysed by LDOX (Yan et al 2005). The clear reduction of Xavonol glycoside accumulation in the ldox Xs1-2 double mutant compared to the Xs1-2 single mutant (Fig.…”
Section: Discussionmentioning
confidence: 96%
“…The Wrst assumption has been shown to be correct in this work and by the work of Owens et al (2008a). The second assumption is based mainly on the work of Turnbull et al (2003Turnbull et al ( , 2004 and Yan et al (2005). In vitro experiments with recombinant LDOX suggested that the enzyme could produce not only its natural product, cyanidin, but depending on the C-4 stereochemistry of the leucocyanidin substrate, possibly also dihydroquercetin and quercetin (Turnbull et al 2003).…”
Section: Discussionmentioning
confidence: 98%
“…The health-promoting effects of flavonoids have stimulated significant research toward the elucidation of their biosynthetic networks, as well as the development of production platforms using well-characterized hosts (8,19). Within this context, Hwang et al recently described recombinant Escherichia coli strains that lead to the synthesis of flavanones, the common precursors of the vast majority of flavonoids (7).…”
mentioning
confidence: 99%